The Effectiveness of Pedagogical Ecocriticism to Enhance Environmental Awareness in Post Pandemic Era - Ahmad Iklil Saifulloh; Syafiul Anam (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This research aims at knowing the implementation of pedagogical ecocriticism to enhance environmental awareness after two years pandemic era shape the teaching and learning process passively. As a quantitative research design, this research tried to reveal the power of pedagogical ecocriticism towards environmental awareness. As a means of pre-experimental research, the researcher pointed a statistic parametric test with paired sample t-test to determine the significance of defectiveness between pedagogical ecocriticism and environmental awareness. SPSS for Windows (Evaluation Version 22) was used for the analysis. The instrument used was the modified instrument from Gerrad (2012) which cover Pollution, Apocalypse, Position, Pastoral, Future, Wilderness, Dwelling, Animist, Sacred Place, Mysticism, and the Earth. There were forty students from the Islamic University of Majapahit Mojokerto, half students from the English Department, and a half from the Indonesian Department. Based on statistical analysis, pearson product-moment was used to correlate the pre-test and post-test, and it shows that the correlation value was .423 and sig. Value was .063. Its means that the significant result; 063 was higher than 005, and (2-tailed) was .000 < 0,005 or .000 is smaller than 0,05. It can be concluded that hypothesis H1 was accepted and H0 was rejected. There is significance result between pedagogical ecocriticism and environmental awareness at the data of pretest and posttest. The final result proved that Ecocriticism has a great significance to pay heed of pedagogical in environmental awareness in general.